(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Collecting and studying the wealth of creativity created by the Uzbek people for thousands of years, passed down from generation to generation, raising the young generation to be spiritually rich, morally pure, and physically fit on the basis of these rich treasures is one of the urgent issues of today